Catalytic alkane transfer-dehydrogenation by PSCOP iridium pincer complexes. (25th September 2016) - Yao, Wubing; Jia, Xiangqing; Leng, Xuebing; Goldman, Alan S.; Brookhart, Maurice; Huang, Zheng
Graphical abstract: New ( t Bu2 PSCOP R2 )IrHCl iridium complexes ligated by hybrid phosphinothious-phosphinite PSCOP ligands have been synthesized and characterized. The steric properties of the pincer ligands prove to have a marked impact on catalytic activities of these complexes in transfer-dehydrogenation of cyclic and linear alkanes. Abstract: A series of new ( t Bu2 PSCOP R2 )IrHCl iridium complexes with 'hybrid' phosphinothious-phosphinite PSCOP ligands ([ t Bu2 PSCOP R2  = 1-(SP t Bu2 )-3-(OPR2 )-C6 H4 ], R =  t Bu, 4a, R = Cy, 4b, R =  i Pr, 4c, and R = Et, 4d ) have been synthesized and characterized. Treatment of complexes4a –d with sodium tert -butoxide generates the active species for catalytic transfer-dehydrogenation of cyclooctane (COA) or n -octane using tert -butylethylene (TBE) as hydrogen acceptor to form cyclooctene (COE) or octenes, respectively. The catalytic activity of these complexes and the product selectivity in alkane dehydrogenation is greatly influenced by the steric properties of the pincer ligand. In general, the less sterically bulky complex exhibits higher catalytic activity than the more hindered complex. Among the new (PSCOP)Ir-type complexes, the least crowded complex ( t Bu2 PSCOP Et2 )IrHCl4d is most active for n -octane/TBE transfer-dehydrogenation. The relatively crowded, less active, complexes ( t Bu2 PSCOP t Bu2 )IrHCl (4a ) and ( t Bu2 PSCOP Cy2 )IrHCl (4b ) exhibit high regioselectivity for α-olefin formation at the early stages of the reaction.